2021
DOI: 10.3389/fenvs.2021.784751
|View full text |Cite
|
Sign up to set email alerts
|

The Interannual Variability of the Fall Size of Young-of-The-Year Chub (Squalius cephalus): Influence of Phenology, Growth Patterns and Abiotic Factors

Abstract: Long-term surveys confirm the rapidity of environmental and biological changes undergone by endangered species but that also concerned relatively “tolerant” species, especially common rheophilic species such as European chub (Squalius cephalus, Linnaeus 1758). As many organisms, fish are highly vulnerable during their first life stages. Body size is a determinant factor for ecosystem functioning and for fish to survive to predators or to winter conditions. While numerous studies has already demonstrated the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Trophic webs are complex and fragile, especially when encompassing YOY of predatory fish species. These stages are indeed less resilient because they need to maximise growth (Miller et al, 1988) during the months after hatching to rapidly exceed predator gape limitations, make ontogenetic shifts, and increase survival by reaching a sufficient size to escape harsh environmental conditions (Cowan et al, 2000; Logez et al, 2021). We found that YOY had segregated trophic niches and identified some general patterns, especially in the trophic positioning, with perch always in a lower position than pike and pikeperch.…”
Section: Discussionmentioning
confidence: 99%
“…Trophic webs are complex and fragile, especially when encompassing YOY of predatory fish species. These stages are indeed less resilient because they need to maximise growth (Miller et al, 1988) during the months after hatching to rapidly exceed predator gape limitations, make ontogenetic shifts, and increase survival by reaching a sufficient size to escape harsh environmental conditions (Cowan et al, 2000; Logez et al, 2021). We found that YOY had segregated trophic niches and identified some general patterns, especially in the trophic positioning, with perch always in a lower position than pike and pikeperch.…”
Section: Discussionmentioning
confidence: 99%
“…The growth rates of right otoliths were estimated based on the method described in previous studies (Bounket et al, 2019(Bounket et al, , 2021Logez et al, 2021). Briefly, to expose the daily increments, the otolith was embedded in epoxy resin (Araldite 2020) and ground along the frontal plane using abrasive papers and diamond solutions.…”
Section: Otolith Growth Ratementioning
confidence: 99%